Male gonadal denervation by guanethidine at pre-puberty: Different doses, different results. The intervention of the pineal deafferentation - Guimaraes, M. A.; Lunardi, L. O.; Pellizzon, C. H.; Kempinas, W. G.; Silva, AAMRE (Cellular & Molecular Biology, 1997)
Since gonadal denervation and pineal deafferentation by cervical superior ganglionectomy affect sexual development, this study was performed to evaluate testicular steroidogenesis, spermatogenesis and the cervical superior ganglion (CSG) histology in rats treated with guanethidine (GD). The treatment was performed by GD s.c. injections for 3 weeks, from the 21st day of age to the 41st day of age (pre-puberty), when the animals were sacrificed. Different doses were used: group A=10 mg/kg/day, group B=50 mg/kg/day and saline (control group). Testicular denervation was confirmed by HPLC for catecholamines in testicular tissue. Testicular concentrations (TC) of progesterone (P4) and testosterone (T) were measured by RIA. Significantly higher TC of P4 and lower TC of T were observed only in group A in comparison with group B and the control group. No alteration of sperm production was observed in either treated group. Histological analysis of CSG showed only few neuronal alterations in group A rats, while in group B the nervous cells were practically destroyed. This suggests that 10 mg/kg/day GD treatment probably produces a specific blockade of 17 alpha-hydroxylase/17,20 desmolase at pre-puberty leading to a decrease of the androgen production. However, in the 50 mg/kg/day group no differences were observed concerning the steroid profiles, this result being attributed to the extensive damage to the CSG observed only in group B. The CSG destruction causes deafferentation of the pineal gland producing abolishment of the inhibition of the 17 alpha-hydroxylase/17,20 desmolase promoted by melatonin or by an out of phase production of androgen.
Keywords: pre-puberty; progesterone; testosterone; cervical superior ganglion; 17 alpha-hydroxylase 17,20-desmolase; pineal deafferentation